An Analysis of Slang Words Used in Fast and Furious 9 Movie - Putri, Elisa Anggita; Novari, Ari Fajria; Munawaroh, Tatu (Journal of English Education Studies, 2023)
This research deals with An Analysis of Slang Words in Fast and Furious 9 Movie. The purpose of this study was to determine the type and meaning of the slang used in Fast and Furious 9 movie. The data source is taken from the script Fast and Furious 9 movie. The Fast and Furious 9 movie classified as American action movie released in April 2017 and directed by F. Gary Gray and written by Chris Morgan. The research design used in this research is descriptive qualitative research. This research is described one by one slang words are found from the film Fast and Furious 9 movie by using dictionaries and theories related to slang. From the analysis, there are two types of slang, namely society slang and public house slang. There are 24 word of society slang and 6 word of public house slang. Then the slang word in the form of words and phrases are classified and analyzed. These findings suggest that there are several slang words and phrases in Fast and Furious 9 movie that have been classified into a type of slang. Examples as well as slang words that often appear are Shit, Damn it, Guys.Buddy and Bro. This study is expected to contribute to the reader to found out about slang clearly. This can help readers speak English fluently. And it can too is expected to enrich new English vocabulary used in everyday conversation.